DILATED CARDIOMYOPATHY DENGAN INTRAKARDIAK TROMBUS BERKOMPLIKASI PADA STROKE NON HEMORAGIK: CASE REPORT - Pande, Ni Nyoman Utami Wijayaswari; Gunawijaya, Eka; Yantie, Ni Putu Veny Kartika; Dewangga, Made Satria Yudha (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Patients with DCMP have been reported to have abnormalities in platelet function and reduced LVEF that contribute to hypercoagulability and stasis conditions that have been described as predisposing to intracardiac thrombus formation. Cases have been described of patients with DCMP who had an initial clinical presentation of thrombus at the LV apex and with thromboembolic events. The patient was treated in the pediatric intensive care unit with anticoagulant therapy and heart failure.